Perlindungan Hukum Bagi Pemilik Merek Tidak Terdaftar - Nadia Irvan; Rory Jeff Akyuwen; Agustina Balik (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: In Indonesia, trademark rights can be obtained after registering a trademark. However, there are still many business actors who have not registered their trademarks due to a lack of understanding about brands.Purposes of the Research: The purpose of this study is to analyze and examine the legal protection for unregistered trademark owners in Ambon City. Methods of the Research: The method used in analyzing and reviewing is normative juridical using a conceptual framework and legal materials derived from literature studies to solve problems qualitatively.Results of the Research: The results of this study indicate that the brand is a distinguishing mark that must be protected. However, in Indonesia it only protects registered trademarks, it is hoped that in the future Indonesia can provide fair and equitable legal protection for a brand through a combined protection system between a declarative system and a constitutive system. The combined protection system which is intended as a right to a mark is granted to the first user of a mark provided that the first user can prove that he is the first user, and registration is proof of use.